Great variability in nest lining size: support for thermoregulation but not for anti-predatory adaptation hypothesis - Kubelka, Vojtěch; Sládeček, Martin; Šálek, Miroslav (Journal of ornithology, 2019)
Nest lining is a key component in nests of many bird species. Among ground-nesting birds with open nests, it usually consists of dry sticks and stalks creating a thermoregulatory insulating layer for the eggs. However, a bigger nest lining can attract predators and increase nest mortality. The factors influencing behavioural plasticity in birds facing the trade-off between nest lining thermoregulation and conspicuousness for predators have remained poorly understood. The Northern Lapwing Vanellus vanellus , a visibly incubating shorebird with an active nest defence against potential predators, demonstrates great variability in the size of nest lining and, at the same time, is subject to a high frequency of nest predation. We analysed the variability of nest-lining size across time and space in 915 measurements of 601 lapwing nests in South Bohemia, Czech Republic, during 2010–2015. We show that lapwing nests placed closer to small water pools with generally cooler microclimates had bigger nest lining. The size of nest linings also reflected the availability of nest lining material in the vicinity of the nest. On the other hand, there was no effect of nest position within the breeding association and distance to the nearest perch as a possible stand for predators on nest lining size. Furthermore, nest lining size did not predict nest predation rate. Our findings suggest that lapwings adjust the size of their nest lining to local microclimate conditions rather than potential predation risk which is in concordance with the thermoregulation hypothesis of the nest size in birds.